Effect of Dy doping on the properties of La-Ca-Mn-O ceramics - Sharif, Sharmiwati Mohd; Shaari, Abdul Halim; Lim, Kean Pah; Kabashi, Kabashi Kathir; Yunus, Wan Mahmood Mat; Chik, Abdullah; Zainuddin, Hishamuddin (Penerbit Universiti Sains Malaysia, 2004)
The discovery of colossal magnetoresistance (CMR) has received attention since 1950s. As the name applies, these materials show huge change in electrical resistivity with the applied magnetic field. The CMR material usually described with the formula Ln1-xAxMnO3 where Ln usually the trivalent rare earth ions (La3+, Pr3+, Nd3+, etc.) and A is the divalent ions (Ca2+, Ba2+, Sr2+). It is commonly found that the CMR material has a temperature-dependent behavior of resistance at zero-field and the largest CMR effect appears at insulator-metal (I-M) transition.